Pandemic Awareness and Caring Behaviors of Nurses Working in Intensive Care Unit – A Multicenter Study - Demir, Burcu Dedeoğlu; TÜREN, SEVDA; Doğan, Derya Akça (Publishing Office of the University of Rzeszow, 2023)
Introduction and aim. In the COVID-19 pandemic, which is a global threat, the awareness levels of intensive care nurses who meet all the care needs of patients can affect the quality of care. In this study, pandemic awareness and care behaviors of nurses who undertook the patient’s care needs in intensive care units were examined. Material and methods. The research was carried out with 317 nurses working critical care units of 12 hospitals in different provinces. “Nurse Characteristics Form”, “Pandemic Awareness Scale” and “Caring Behaviors Inventory-24” were used as data collection tools. Data were collected between March and August 2022 in the middle of the COVID-19 pandemic process using an online survey. Results. It was determined that 75.4% of the participants were female and the mean age was 25.56±4.49. Pandemic awareness scale score was 3.04±0.62 (0.11-3.67) and caring behaviors inventory score was 5.48±0.84 (1.00-6.00). A significant, positive, weak relationship was found between nurses’ pandemic awareness and all sub-dimensions of caring behaviors (p≤ 0.05). Conclusion. It was seen that the caring behaviors of nurses with high pandemic awareness were also positively affected. Although it was the first time they had experienced the pandemic, nurses were found to have good caring behaviors.
Keywords: Caring Behavior; Intensive Care; Nurse; Pandemic Awareness